Mechanical property evaluation of bamboo fiber reinforced epoxy composite - Radin Mohd Ali Radin, Bahrom (2009)
Natural fiber has emerged as a renewable and cheaper substitute to synthetic fiber which is use as reinforcement material. The main objective of this study is to investigate the performance of bamboo fiber reinforced epoxy composite and to investigate the mechanical property of bamboo fiber reinforced composite with different fiber orientation. This analysis was carried out by using commercial Finite Elements software (ALGOR) to evaluate the behavior of the composite. Tensile and flexural test was carried out to obtain tensile and flexural strength of the composite. Three type of composite with different fiber orientation were tested in this project. Unidirectional composite was found had a higher tensile strength and multidirectional composite had higher flexural strength. From the observation, increasing the number of layer in the composite, the value of tensile strength will decrease but the value o flexural strength will increase. Thus, the tensile strength of bamboo fiber composite is depends on the degree of the orientation of the fiber. For the flexural strength of bamboo fiber composite, it depends on the number of layer or thickness of the composite.